Drought-mediated oxidative stress and its scavenging differ between citrus hybrids with medium and late fruit maturation - Jin Jia; Mingjiong Zhao; Rui Liu; Caixin Xue; Zhuyuan Xia; Bin Hu; Heinz Rennenberg (Plant Stress)
Drought stress is a major environmental factor limiting citrus productivity. Still, differences in drought sensitivity between citrus hybrids of different maturation periods have so far not been reported. Here, we selected a medium-maturing (Fertile orange: FO (Citrus reticulata cv. Fertile orange) and a late-maturing citrus hybrid (Newhall Navel orange: NO (Citrus sinensis Osbeck cv. Newhall) and determined the physiological and biochemical traits of leaves, roots, wood and bark. Our results showed that drought significantly decreased net photosynthetic rate (Pn), stomatal conductance (Gs) and transpiration rate (Tr) of citrus leaves. Oxidative stress upon drought was indicated by enhanced foliar malondialdehyde (MDA) and hydrogen peroxide contents, as well as a stimulation of the anti-oxidative system. This stimulation included the contents of dehydroascorbic acid (DHA), glutathione (GSH) and oxidized glutathione (GSSG) in leaves, roots, wood and bark, as well as activities of antioxidative enzymes of glutathione reductase (GR), dehydroascorbate reductase (DHAR), superoxide dismutase (SOD) and peroxidase (POD). The late maturing NO hybrid not only showed better general physiological performance as indicated by increased Pn in leaves, but also higher biochemical ROS scavenging and osmotic capacity as indicated by increased ascorbic acids (ASA), DHA, and proline contents, as well as activities of enzymes of SOD, POD, ASA/DHA and GSH/GSSG ratios in the investigated tissues compared to the FO hybrid under drought and control conditions. Analysis of molecular mechanisms of signaling, regulatory and functional genes expression are suggested for future studies to elucidate the complex interplay of molecular, biochemical and physiological responses of citrus hybrids to drought.